Safety management : near miss identification, recognition, and investigation - McKinnon, Ron C. (Boca, Raton, FL : CRC Press, 2012)
'Identification and investigation of'near-miss' incidents can be the difference between avoiding and suffering a drastic, loss-producing accident. This book provides a step-by-step program on how to develop a'near-miss' incident program in the workplace to isolate and eliminate root causes, heal systemic weaknesses, and instill safety management systems before an accident occurs. Focusing on the successes of such safety systems at two large copper mines, numerous diverse industries, and an aluminum smelter, it includes several examples and case studies to clarify the investigative philosophy and preventive application of'near-miss' incidents'--
'Research over the years has indicated that before a loss-producing accident occurs there are many warnings in the form of near miss incidents which often go unheeded. This book shows how by identifying the near miss incidents and investigating them in an effort to identify and eliminate the root causes, subsequent accidents can be prevented. Focusing on the near misses gives organizations the opportunity to identify weaknesses in the safety management systems before an accident occurs rather than after the event'--
Includes bibliographical references and index.
Keywords: Industrial safety -- Management; Industrial accidents; Accident investigation